Discovery and structure activity relationship of glyoxamide derivatives as anti-hepatitis B virus agents. (1st February 2021) - Amblard, Franck; Boucle, Sebastien; Bassit, Leda; Chen, Zhe; Sari, Ozkan; Cox, Bryan; Verma, Kiran; Ozturk, Tugba; Ollinger-Russell, Olivia; Schinazi, Raymond F.
Graphical abstract: Abstract: Chronic hepatitis B viral infection is a significant health problem world-wide, and currently available antiviral agents suppress HBV infections, but rarely cure this disease. It is presumed that antiviral agents that target the viral nuclear reservoir of transcriptionally active cccDNA may eliminate HBV infection. Through a series of chemical optimization, we identified a new series of glyoxamide derivatives affecting HBV nucleocapsid formation and cccDNA maintenance at low nanomolar levels. Among all the compounds synthesized, GLP-26 displays a major effect on HBV DNA, HBeAg secretion and cccDNA amplification. In addition, GLP-26 shows a promising pre-clinical profile and long-term effect on viral loads in a humanized mouse model.